Near-infrared triggered Ti3C2/g-C3N4 heterostructure for mitochondria-targeting multimode photodynamic therapy combined photothermal therapy. (October 2020) - Zhang, Yiyi; Cheng, Yaru; Yang, Fan; Yuan, Zhipeng; Wei, Wei; Lu, Huiting; Dong, Haifeng; Zhang, Xueji
Graphical abstract: We report a two-dimensional heterostructure Ti3 C2 /g-C3 N4 -TPP near-infrared (NIR) photosensitizers, which consists of electrostatically assembled Ti3 C2 and g-C3 N4 with surface further modification of TPP. After endocytosis, the Ti3 C2 /g-C3 N4 -TPP specially target mitochondria. Under a 670 nm irradiation, Ti3 C2 /g-C3 N4 -TPP enables produce superoxide radicals (·O2 − ) and hydroxyl radicals (· OH) through electron transfer following an oxygen-independent type I mechanism PDT. In addition, it also enables be triggered to split endogenous water to produce abundant O2 for singlet oxygen ( 1 O2 ) generation through energy transfer for oxygen self-supplement type II mechanism PDT. As a result, a multimode enhanced PDT is performed under both normoxic and hypoxic conditions. Furthermore, the Ti3 C2 /g-C3 N4 -TPP also exhibited excellent photothermal effect derived from Ti3 C2 for PTT, leading to superb anticancer efficacy. Highlights: Two-dimensional Ti3 C2 /g-C3 N4 -TPP heterostructure for mitochondria-targeting multimode PDT and PTT. Ti3 C2 /g-C3 N4 -TPP could trigger endogenous water-splitting to produce abundant O2 . Ti3 C2 /g-C3 N4 -TPP simultaneously achieves oxygen self-supplement type II PDT and oxygen-independent type I PDT. The synergistic cytotoxic ROS generation and photothermal damage at mitochondria efficiently inhibit tumor growth. Abstract: g-C3 N4 is promising photosensitizer (PS) for photodynamic therapy (PDT) because of its reactive oxygen species (ROS) generation ability. However, satisfactory photocatalytic activity and visible light response limit its effectiveness in in vivo therapy. Herein, we report a near-infrared (NIR)-responsive two-dimensional Ti3 C2 /g-C3 N4 heterostructure for in situ oxygen-generating enhanced multimode PDT and photothermal therapy (PTT). We demonstrate that the assembly of Ti3 C2 to g-C3 N4 significantly extend the absorption of g-C3 N4 to NIR region and enhance the photocatalytic activity owing to the improved photogenerated carrier separation compared to free g-C3 N4 . After further modification of triphenylphosphonium bromide (TPP) on Ti3 C2 /g-C3 N4, and the mitochondria-targeting Ti3 C2 /g-C3 N4 -TPP enables produce oxygen-independent ·O2 − - and · OH through electron transfer. Moreover, it also achieves oxygen self-supplement 1 O2 generation through energy transfer on account of its ability of photocatalytic split endogenous water. As a result, a multimode enhanced PDT is performed under both normoxic and hypoxic conditions. Ti3 C2 /g-C3 N4 -TPP also shows good photothermal performance derived from Ti3 C2 for PTT. This work expands the g-C3 N4 -based PDT application, contributing to design photocatalytic nanomaterials with desired absorption to overcome the limitation of tumor hypoxia.